" Determinants of nursery pupils’ acquisition of basic language skills in Rivers state, Nigeria " (2013)
In this study, the researchers investigated the effect of teaching method (jolly phonics) and school characteristics (material provision, class size, teacher qualification, pupils’ gender and school location) on nursery three pupils’ acquisition of basic language skills (listening, speaking, reading and writing). Survey design was adopted and purposive sampling technique was used to select 400 pupils from 40 schools (20 private and 20 public schools) in urban and rural locations in Rivers State. Ten pupils, (five boys and five girls) were randomly selected from each school. Data collection involved the use of Basic language skill test (BLST) and instructional material checklist (IMC). Data collected was analyzed using t-test and multiple regression, at p<0.05 significant level. Results revealed that significant mean difference (df = 398; t-crit = 1.96; t-cal= 12.651; p < 0.05) existed between the two groups. The mean difference of the effect of material provision was also significant (df = 398; t-crit = 1.96; t- cal= -2.641; p<0.05). The six school variables’ significantly explained the variance in the pupils’ acquisition of basic skills with multiple regression of .768 and R2= .589 accounting for 59% of variance in the dependent variables. Class size (P = -.629; p < 0.05) and teaching method (P = -.246; p<0.05) made significant contribution to the acquisition of basic language skills. It is concluded that class size and teaching method are important factors that influence the acquisition of basic language skills. It is therefore expedient that policy makers, government, school heads and others who are in the position to see to the welfare of early childhood education pay more attention to these factors.